2005
DOI: 10.1116/1.2050671
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Cu degradation using in situ N2 plasma treatment in a dual-damascene process

Abstract: Articles you may be interested inOn the pressure effect in energetic deposition of Cu thin films by modulated pulsed power magnetron sputtering: A global plasma model and experimentsThe surface state of copper after an etching process using CF 4 gas has been analyzed. Copper surface stability against corrosion is evaluated through a storage test performed under high-humidity conditions after the etching process. The storage test reveals that the copper surface suffered from both corrosion and oxidation. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…This discrepancy may be attributed to the instability of CuF 2 and fluorocarbon (CF x ) on metallic Cu. Previous studies on the dry etching process of Cu using CF 4 gas have shown that CuF 2 and CF x on Cu are highly unstable and decompose to Cu 2 O in a high humidity (80%) atmosphere . The electrochemical reactions at the Cu-IL/Pt interface in the present IL-PRD are strongly influenced by H 2 O, as mentioned earlier.…”
Section: Resultssupporting
confidence: 61%
“…This discrepancy may be attributed to the instability of CuF 2 and fluorocarbon (CF x ) on metallic Cu. Previous studies on the dry etching process of Cu using CF 4 gas have shown that CuF 2 and CF x on Cu are highly unstable and decompose to Cu 2 O in a high humidity (80%) atmosphere . The electrochemical reactions at the Cu-IL/Pt interface in the present IL-PRD are strongly influenced by H 2 O, as mentioned earlier.…”
Section: Resultssupporting
confidence: 61%
“…Increasing the treatment time to 30 s improves the adhesion. Moreover, the tested sample with 30 s NH 3 treatment had a higher adhesion strength than the H 2 -treated sample because the former treatment forms Cu-N chemical bonds [14,15]. The adhesion strength between the Cu film and the barrier layer in H 2 -treated samples did not vary significantly with the treatment time.…”
Section: Resultsmentioning
confidence: 92%
“…The N 2 plasma treatment achieves a defluorination effect on NiSi x after the etching process. These phenomena are thought to be equal with the phenomena of our previous report at the copper surface [10]. Likewise, it is thought that the nitrogen ions play a role to sputter the fluorine residues and the fluorine residues are removed as volatile matter after the reaction with nitrogen.…”
Section: (B)(d) This Indicates Thatmentioning
confidence: 61%